UPLC-ESI-MRM/MS for Absolute Quantification and MS/MS Structural Elucidation of Six Specialized Pyranonaphthoquinone Metabolites From Ventilago harmandiana - Limjiasahapong, Suphitcha; Kaewnarin, Khwanta; Jariyasopit, Narumol; Hongthong, Sakchai; Nuntasaen, Narong; Robinson, Jonathan L.; Nookaew, Intawat; Sirivatanauksorn, Yongyut; Kuhakarn, Chutima; Reutrakul, Vichai; Khoomrung, Sakda (Frontiers in Plant Science, 2021)
Abstract Pyranonaphthoquinones (PNQs) are important structural scaffolds found in numerous natural products. Research interest in these specialized metabolites lies in their natural occurrence and therapeutic activities. Nonetheless, research progress has thus far been hindered by the lack of analytical standards and analytical methods for both qualitative and quantitative analysis. We report here that various parts of Ventilago harmandiana are rich sources of PNQs. We developed a UPLC-ESI-MRM/MS method to quantitatively determine six PNQs from leaves, root, bark, wood, and heartwood. The addition of standards in combination with a stable isotope of salicylic acid-d6 was used to overcome the matrix effect with average recovery of 82±1% (N=15). The highest concentration of the total PNQs was found in the root (11,902 µg/g DW) whereas the lowest concentration was found in the leaves (28 µg/g DW). Except for the root, PNQ-332 was found to be the major compound in all parts of V. harmandiana, accounting for ~48% of the total PNQs quantified in this study. But PNQ-318A was the most abundant PNQ in the root sample, accounting for 27% of the total PNQs. Finally, we provide novel MS/MS spectra of the PNQs at different collision induction energies: 10, 20, and 40 eV (POS and NEG). For structural elucidation purposes, we propose complete MS/MS fragmentation pathways of PNQs using MS/MS spectra at collision energies of 20 and 40 eV. The MS/MS spectra along with our discussion on structural elucidation of these PNQs should be very useful to the natural products community to further exploring PNQs in V. harmandiana and various other sources.